Non-chemical control of fungal pathogens in crops: a one-health perspective on strategies, mechanisms, and future directions - Adkar-Purushothama, Charith Raj; Chettimada, Ashish; Murali, Thokur Sreepathy; Muthusamy, Annamalai; Bouarab, Kamal; Perreault, Jean-Pierre (Frontiers in Plant Science, 2026)
Fungal pathogens threaten global crop production, food security, and environmental and human health. Though the reliance on chemical fungicides has provided effective control, but raises concerns over environmental contamination, toxic residues, and the rapid emergence of fungicide-resistant strains. These challenges, along with regulatory pressures, highlight the need for safer, more sustainable disease-management strategies. This review incorporates advances in non-chemical approaches for controlling fungal plant diseases, including cultural practices, biological control agents, natural plant metabolites, RNA-based technologies, nanotechnology, and microbiome engineering. We evaluate each strategy’s mechanisms, strengths, limitations, and remaining knowledge gaps. An integrated pest management framework is proposed to combine complementary methods, reduce dependence on chemical inputs, enhance crop resilience, and support human and ecosystem health.